Business networking in social media - a case study of Polish export professionals - Deszczynski, Bartosz (Journal of Eastern European and Central Asian Research (JEECAR), 2018)
The article offers a literature review on the role of trust in the business relationship development. It describes the role of social media in the cognitive and affective trust building. The focal point of the article is devoted to an empirical research covering the use of LinkedIn and GoldenLine professional social media platforms by Polish export professionals. It indicates their overall passivity in maintaining a trusty online appearance, but it also touches the limitations of social media communications. The article gives also some managerial recommendations dealing social media B2B involvement and argues that in predictable future the deployment of social media in business networking will remain in its infancy.